The visuality in “Rimbaud”, by Chacal: a semiotic analysis - Mirage, Amanda Nakata (Estudos Semióticos, 2023)
This paper proposes to present, on the basis of a “Rimbaud” by Chacal analysis, a reflection on the visuality in poetry within the domain of structural semiotics. For this purpose we use the theoretical and methodological proposition of Pondian described in “Grammar of written poetry: rhetorical figures”. As a result, we identify the main meaning effects created by the exploration of resources at the poem’s graphic-visual expression plane level and the specificity of the communication receiver built from this. At the end we highlight the relevance of the visuality on poetry studies, markedly from the paradigms set by the modern avant-garde of nineteenth to twentieth century transition, in the poetry domain.